Honorary Members (The American Institute of Mining, Metallurgical, and Petroleum Engineers, 1928)
YEAR OF ELECTION 1913. FRANK DAWSON ADAMS Montreal, Canada. 1921. WILLIAM CUTHBERT BLACKETT Sacriston, Durham, England. 1923.. GELASIO CAETANI Rome, Italy. 1920. HENRY STURGIS DRINKER Merion Station, Pa. 1921. FERDINAND FocH Paris, France. 1922. FEDERICO GIOLITTI Torino, Italy. 1906. SIR ROBERT A. HADFIELD London, England. 1921. FRANK WILLIAM HARBORD London, England. 1917. HERBERT HoovER Washington, D. C. 1905. HENRI LECHATELIER Paris, France. 1921. C. McDERMID London, England. 1913. EZEQUIEL ORDONEZ Mexico City, Mexico. 1909. ALEXANDRE POURCEL Paris, France. 1911. ROBERT H. RICHARDS Cambridge, Mass. 1891. DR. ING. H. C. EMIL SCHROEDTER Mehlem a Rhein, Germany. HONORARY MEMBERS (Deceased)